A case of sepsis due to a rare carbapenem-resistant Ignatzschineria species. (2022) - Maniam, Kali; Argentine, Sarah
Abstract: Ignatzschineria species have emerged only recently and few cases have been identified worldwide. It has been determined that maggots likely serve as the vector of transmission and the majority of cases described involved cutaneous myiasis. This article presents the first case of an Ignatzschineria species closely related to I. larvae/I. ureclastica causing bacteremia in North America. This isolated Ignatzschineria species is also unique in its broad antimicrobial resistance pattern to carbapenem antimicrobials, an uncommon finding among global Ignatzschineria isolates. Improving the ability to identify Ignatzschineria species is an important step to develop the necessary CLSI breakpoints and treatment guidelines. The paucity of information regarding Ignatzschineria species and the inability to accurately identify these organisms indicate the need for more research and improved identification techniques of this emerging pathogen.